Gender Disparities in the Presentation of Gallbladder Disease. Issue 8 (August 2019) - Bailey, Kimberly Shilling; Marsh, Wallis; Daughtery, Levi; Hobbs, Gerry; Borgstrom, David
Although gallbladder disease (GBD) is more common in females, we have noticed a trend toward more complicated cases in male patients. We reviewed all cholecystectomies performed at our institution over the last five years. After eliminating cases with confounding variables, we identified 1529 records. Charts were reviewed for age, gender, BMI, procedure performed, operative time, length of stay, and preoperative diagnosis. Descriptive and inferential statistical analyses were conducted along with linear regression. There were 1444 laparoscopic, 64 laparoscopic converted to open, and 21 primary open cases. Patients were 1008 (66%) females and 521 (34%) males. Average operative time was 89.8 minutes. Cholecystectomy averaged 17.7 minutes longer in males ( P = 0.0046). Two per cent of female patients and 7.9 per cent male patient converted to open. Males were more likely to have complicated GBD, whereas women had uncomplicated disease. Average age was 51.9 years for males versus 42.7 years for females. Age, gender, BMI, length of stay, and preoperative diagnosis were all independently significant in predicting operative time. In our study, women presented with uncomplicated GBD, whereas men presented with complicated GBD. This suggests that male patients present at a later stage of disease.